2015
DOI: 10.1088/0004-637x/804/1/22
|View full text |Cite
|
Sign up to set email alerts
|

A Radio-Polarization and Rotation Measure Study of the Gum Nebula and Its Environment

Abstract: The Gum Nebula is 36 • -wide shell-like emission nebula at a distance of only ∼ 450 pc. It has been hypothesised to be an old supernova remnant, fossil H II region, wind-blown bubble, or combination of multiple objects. Here we investigate the magneto-ionic properties of the nebula using data from recent surveys: radio-continuum data from the NRAO VLA and S-band Parkes All Sky Surveys, and H α data from the Southern H-Alpha Sky Survey Atlas. We model the upper part of the nebula as a spherical shell of ionised… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 129 publications
1
45
0
Order By: Relevance
“…Our highest RM values exceed those published for sources behind Galactic H II regions. Vallée & Bignell (1983), Purcell et al (2015), and Ma et al (2019) reported |RM | up to 633 rad m −2 behind the Gum nebula. Harvey-Smith et al (2011) found |RM | 300 rad m −2 behind a sample of large-diameter, high-latitude, H II regions.…”
Section: Resultsmentioning
confidence: 94%
“…Our highest RM values exceed those published for sources behind Galactic H II regions. Vallée & Bignell (1983), Purcell et al (2015), and Ma et al (2019) reported |RM | up to 633 rad m −2 behind the Gum nebula. Harvey-Smith et al (2011) found |RM | 300 rad m −2 behind a sample of large-diameter, high-latitude, H II regions.…”
Section: Resultsmentioning
confidence: 94%
“…Chanot & Sivan 1983). Its origin is still debated, although most authors suggest that the nebula is likely an old supernova remnant (Woermann et al 2001;Purcell et al 2015). The Gum nebula is located about 500 pc from us, straddles the plane of the Milky Way (extending from l ∼-15 • to l ∼+15 • ), and our line of sight in its direction overlaps with a number of different objects (Fig.…”
Section: The Large-scale Structure and The Iras Vela Shellmentioning
confidence: 89%
“…Vallee & Bignell (1983) modelled the Gum nebula as a magnetic bubble close to the Sun, using 32 RMs that lie within 30 • of the centre of the Gum nebula. More recently, Purcell et al (2015) modelled the Gum nebula as an H ii region around a wind-blown bubble. RMs in the top part of the Gum nebula, which Purcell et al used in their analysis, show a clear transition from inside the edge of the bubble (strong Hα emission) to outside, over a very small distance (see fig.…”
Section: Resultsmentioning
confidence: 99%